Attitude, Risk Perception and Readiness of Ethiopian Potential Migrants and Returnees Towards Unsafe Migration - Minaye, Abebaw; Zeleke, Waganesh A. (African Human Mobility Review, 2021)
In Ethiopia, where there is high prevalence of migration to the Middle East andEurope, a multitude of studies have focused on the relationships between the roleof smugglers, push and pull factors, and illegal migration. However, only afraction of studies have examined the context from the individual and collectivemind-set perspective. The process of the decision to migrate may be influencedby individuals’ beliefs about illegal migration. This study examined the attitudes,levels of readiness and risk perceptions of potential and returnee migrantstowards illegal migration to the Middle East. Survey data were collected from1,726 Ethiopian returnee (n=991) and potential migrants (n=735). Resultsindicated that here was a significant difference between potential and returneemigrants in holding a positive attitude towards unsafe and illegal migration, t(1260) =-8.474, p=0.000.